Impact of national influenza vaccination strategy in severe influenza outcomes among the high-risk Portuguese population - Machado, Ausenda (2020)
Resumo da comunicação publicado em: ESCAIDE 2019: abstract book, p. 44. Disponível em: https://www.escaide.eu/sites/default/files/documents/ESCAIDE-abstract-book-2019.pdf